Scandalize my name : black feminist practice and the making of black social life - Williamson, Terrion L. (Commonalities, 2017)
From sapphire, mammy, and jezebel, to the angry black woman, baby mama, and nappy-headed ho, black female iconography has had a long and tortured history in public culture. The telling of this history has long occupied the work of black female theorists-much of which has been foundational in situating black women within the matrix of sociopolitical thought and practice in the United States. Scandalize My Name builds upon the rich tradition of this work while approaching the study of black female representation as an opening onto a critical contemplation of the vagaries of black social life. It makes a case for a radical black subject-position that structures and is structured by an intramural social order that revels in the underside of the stereotype and ultimately destabilizes the very notion of "civil society." At turns memoir, sociological inquiry, literary analysis, and cultural critique, Scandalize My Name explores topics as varied as serial murder, reality television, Christian evangelism, teenage pregnancy, and the work of Toni Morrison to advance black feminist practice as a mode through which black sociality is both theorized and made material.